On the classical theories of non-democratic regimes and their usefulness in examining Eastern Europe 1944–1989 - Kubát, Michal (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
This study examines the classical theories of non-democratic regimes from the perspective of their possible qualifications as well as practical applicability. In the first part of this paper, the two main conceptions — totalitarianism and authoritarianism — as well as their modifications are investigated. The purpose of this investigation is to clear up some of the misconceptions associated with these terms. In the following part of the paper, the link between these theories and political practice is examined, both from a theoretical and practical point of view. In this respect, the author turns in his analysis predominantly to postwar communist Eastern Europe. The main aim of this paper is to back up these classic conceptions of political science, show their theoretical meaning and usefulness in practice.
Keywords: totalitaryzm; autorytaryzm; quasi-totalitaryzm; Europa Wschodnia 1944-1989